2017
DOI: 10.1038/emm.2017.255
|View full text |Cite
|
Sign up to set email alerts
|

Complex roles of the stroma in the intrinsic resistance to gemcitabine in pancreatic cancer: where we are and where we are going

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is among the most devastating human malignancies. The poor clinical outcome in PDAC is partly attributed to a growth-permissive tumor microenvironment. In the PDAC microenvironment, the stroma is characterized by the development of extensive fibrosis, with stromal components outnumbering pancreatic cancer cells. Each of the components within the stroma has a distinct role in conferring chemoresistance to PDAC, and intrinsic chemoresistance has further worsened this pessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 121 publications
3
97
0
2
Order By: Relevance
“…While gemcitabine is still considered as a first-line therapy and is given alone or combined with other agents to attack locally advanced or metastatic pancreatic cancers, the success is very limited and disappointing (5,6,8,47,48). The failure of gemcitabine to attack aggressive pancreatic cancers cells is due to intrinsic (metabolic malfunction) or extrinsic resistance (drug delivery/ desmoplasia) or both to gemcitabine (9,15,47). Thus, multiple studies have been carried out to understand the mechanism, and they gave new insights into the gemcitabine resistance of aggressive cancer cells having cancer stem cell-like properties (47,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While gemcitabine is still considered as a first-line therapy and is given alone or combined with other agents to attack locally advanced or metastatic pancreatic cancers, the success is very limited and disappointing (5,6,8,47,48). The failure of gemcitabine to attack aggressive pancreatic cancers cells is due to intrinsic (metabolic malfunction) or extrinsic resistance (drug delivery/ desmoplasia) or both to gemcitabine (9,15,47). Thus, multiple studies have been carried out to understand the mechanism, and they gave new insights into the gemcitabine resistance of aggressive cancer cells having cancer stem cell-like properties (47,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…The failure of gemcitabine to attack aggressive pancreatic cancers cells is due to intrinsic (metabolic malfunction) or extrinsic resistance (drug delivery/ desmoplasia) or both to gemcitabine (9,15,47). Thus, multiple studies have been carried out to understand the mechanism, and they gave new insights into the gemcitabine resistance of aggressive cancer cells having cancer stem cell-like properties (47,(49)(50)(51). These studies, collectively, suggested that simultaneously targeting intrinsic-and extrinsic-resistant events may increase the toxic effects of gemcitabine and increase patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the stiff stroma was thought to present a physical barrier to drug perfusion, however it is now appreciated that limiting drug delivery is not the only reason pancreatic tumors are therapy resistant (6)(7)(8). The ways in which the stromal cells within pancreatic cancer contribute to PDAC resistance has become an area of intense study, with a recent focus on interaction between stroma and PDAC via direct contact and paracrine signaling (9)(10)(11)(12). A variety of biomolecules secreted by pancreatic stromal cells have been implicated in resistance to radio-and chemotherapy, including cytokines such as SDF-1a and IGFs, extracellular matrix (ECM) proteins such as fibronectin and collagen I, and even exosomes (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above methods, the stroma has also been shown to cause resistance by sequestering gemcitabine, a deoxycytidine (dC) analog (11,18). The mechanism by which gemcitabine causes toxicity in cells in well studied (19).…”
Section: Introductionmentioning
confidence: 99%